Kapabilitas Tata Kelola Sumber Daya Teknologi Informasi pada Dinas Komunikasi dan Informatika Kota Kediri Berdasarkan Pedoman COBIT 5 - Muhamad Adeseno Marantisa; Admaja Dwi Herlambang; Suprapto Suprapto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
The Department of Communication and Informatics of Kediri City is a government agency engaged in public services, communication and informatics. In carrying out these activities, an information technology governance is required that can regulate and control each activity. In addition, human resources also need to be provided and their readiness is ensured in carrying out these activities. Therefore, lack of human resources and ensuring existing IT resources are problems that must be overcome by the company. There is a guideline that can measure the level of capability of existing IT resources, COBIT. This study uses COBIT 5 guidelines to measure the level of IT resource governance capabilities with a focus on the EDM04 - Ensure Resource Optimization and APO07 - Manage Human Resources processes. The data collection methods used in this study were observation, interviews, and direct document review. The results of the measurement of the capability level obtained are in the process of EDM04 - Ensure Resource Optimization at Level 1 with a value of 72.3% in the Largely Achieved (L) category and in the process of APO07 - Manage Human Resources process at Level 1 with a value of 73.2% category Largely Achieved (L). Based on the results of the capability level obtained and the expected level of capability to be at Level 3, so that each process has a gap of 2 levels. Recommendations given in an effort to reach the expected level are focusing on fulfilling documents, monitoring and evaluating existing IT resources, and making policies or monitoring actions on existing human resources.